Modeling the effect of sonication parameters on size and dispersion temperature of solid lipid nanoparticles (SLNs) by response surface methodology (RSM). (May 2014) - Siddiqui, Akhtar; Alayoubi, Alaadin; El-Malah, Yasser; Nazzal, Sami
Abstract The objective of this study was to evaluate the effect of sonication time and pulse frequency on average dispersion temperature (ART), particle size and zeta potential of solid lipid nanoparticles (SLNs). A two-factor, three-level response surface methodology (RSM) was used to optimize sonication time between 5 and 15 min and pulse frequency from 30 to 90%. SLNs made from stearyl alcohol (SA) and cetyl trimethylammonium bromide (CTAB) blend at 1:3 ratio were prepared by applying high-shear homogenization and sonication. Pulse frequency and time were found to have a significant effect on particle size and ART. The effect of sonication parameters on zeta potential, however, was insignificant. The optimal sonication parameters for preparing 100 nm SLNs made from a SA/CTAB blend was 60% pulse frequency at 40% power for 10 min. Optimized sonication parameters were then used to investigate the effect of lipid type on SLN size and zeta potential. The mean particle sizes of SLNs made with SA, cetyl palmitate, Precirol®, Dynasan118® and Compritol® were 98, 190, 350, 350 and 280 nm, respectively. In conclusion, pulse frequency and time were found to be critical for obtaining SLNs with desirable size, whereas the stability of the SLNs was dependent on their lipid content.